Arrangement of Draft Outline of a Regent Regulation as an Operational Regulation of Local Regulation Number 4 Year 2012 about Health of Maternal, Infant, Baby, and Children under 5 years old in District of Hulu Sungai Selatan in Province of South Borneo - Ismayanti Ismayanti; Sutopo Patria Jati; Chriswardani Suryawati (Magister Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2015)
ABSTRAKABSTRAK Implementasi Perda Kabupaten HSS Nomor 4 Tahun 2012 tentang KIBBLA belum dilaksanakan secara optimal, hal ini dikarenakan selama kurun waktu 2 tahun sejak disahkannya Perda KIBBLA, DKK HSS hanya melakukan kegiatan-kegiatan yang masih bersifat himbauan saja tanpa didukung peraturan lain di bawah Perda yang lebih mengikat. Tujuan penelitian mengevaluasi seberapa jauh kinerja implementasi Perda Nomor 4 Tahun 2012 tentang KIBBLA di Kabupaten HSS terkait penyusunan outline draft Peraturan Bupati tentang KIBBLA. Desain penelitian kualitatif disajikan secara deskriptif eksploratif, pendekatan menggunakan teknik non probability sampling dengan purposive sampling. Subjek penelitian 4 orang informan utama yaitu Kepala Dinas Kesehatan, Kabid Kesga, Kasi KIA dan Kasi Gizi, total informan triangulasi sebanyak 24 orang, yang terbagi dalam 2 kelompok yaitu 12 orang berasal dari tenaga kesehatan pelaksana Perda KIBBLA dan 12 orang sasaran Perda KIBBLA. Data dikumpulkan dengan wawancara mendalam (indepth interview) FGD dan workshop, pengolahan data dengan metode analisis isi (content analysis). Hasil penelitian menunjukkan bahwa: 1) evaluasi kinerja implementasi Perda KIBBLA melalui indikator sebagai berikut: a) akses sasaran Perda KIBBLA untuk menjangkau fasilitas dan pelayanan KIBBLA bervariasi tergantung dari letak geografis; b) pelayanan KIBBLA masih belum dapat dijangkau oleh semua kelompok sasaran; c) frekuensi sasaran mendapat pelayanan KIBBLA beragam tergantung dari jenis pemberi pelayanan; d) masih terdapat penyimpangan terhadap penerapan Perda KIBBLA di lapangan; e) pelayanan yang diberikan masih belum sesuai standar; f) akuntabilitas yang dilaksanakan sebatas pada kegiatan rutin; g) keluaran kebijakan yang diterima oleh sasaran masih belum sesuai dengan kebutuhan; 2) telah dilakukan proses identifikasi masalah dan masukan untuk penyusunan Peraturan Bupati dari sasaran dan petugas kesehatan; 3) telah dilakukan perumusan outline draft Perbup, mengenai: wewenang, tanggung jawab Pemda, pelayanan persalinan, jenis tenaga KIBBLA, jenis sarana pelayanan kesehatan dan kualifikasi yang dibutuhkan, tata cara pelaporan, pengaduan, pembentukan unit pengaduan masyarakat dan tata cara verifikasi dan tingkat kesiapan.Kata kunci : Evaluasi kinerja implementasi, Perda KIBBLA, Outline Draft Peraturan Bupati.ABSTRACTThe local regulation Number 4 Year 2012 about health of maternal, infant, baby, and childrenunder 5 years old in District of Hulu Sungai Selatan had not been optimally implemented because it was not supported by other regulation below its regulation since it was approved two years ago. This research aimed to arrange a draft outline of Regent regulation as an operational regulation of the local regulation Number 4 Year 2012 about Health of Maternal, Infant, Baby, and Children under 5 years old in District of Hulu Sungai Selatan in Province of South Borneo. This was qualitative research presented using descriptive-explorative methods. Number of main informants were 4 persons selected using non probability sampling with purposive sampling. They consisted of head of District Health Office, head of family health department, and heads of maternal and child health section and nutritional section. Informants for triangulation purpose were divided into two groups namely 12 health workers and 12 people of target of the local regulation. Data were collected using in-depth interview, FGD, Brainstorming, and workshop. Furthermore, data were analyzed using content analysis.The result of this research showed that: 1) the indicators to evaluate the local regulationimplementation were as follows: a) access to reach service facilities and obtaining the variousservices depended on geographical location; b) the services of Health of Maternal, Infant, Baby, and Children under 5 years old had not been used by all target people; c) frequency of target people who obtained the services varied depending on types of providers; d) there was any irrelevance in implementing the local regulation; e) there was any unstandardized service; f) a form of accountability was only as a routine activity; g) a released policy was not appropriate with necessity of target people. 2) There had been done a process of problem identification and input to arrange the draft outline of the regent regulation from target people and health workers. 3) Some important points that would be written on the draft outline were: authority, local government responsibility, delivery service, types of workers, types of health service means and qualification needed for the services, reporting procedure, complaint, forming a complaint unit and a procedure to verify and level of readiness.Keywords : Performance Evaluation of Implementation, Local Regulation of Health of Maternal, Infant, Baby, and Children under 5 years old, Draft Outline, Regent Regulation